Influence of Company Characteristics on Carbon Disclosure Emissions on Manufacturing Companies in Indonesia - Andala Rama Putra Barusman, Nurdiawansyah, Tri Lestira Putri Warganegara, Selfia Alke Mega (International Journal of Advanced Science and Technology, 2020)
The efforts of the international community to change the phenomenon of change have begun since the signing of the United Nations Framework Convention on Climate Change (UNFCCC) (Kardono, 2010). According to the Intergovernmental Panel on Climate Change (IPCC), average global temperatures are increasing at a rate of 0.740C ± 0.180C which is increasing climate change in various places including in Indonesia. This study aims to determine whether the company size, age of the company, profitability, and institutional ownership of the company regarding the disclosure of carbon emissions in manufacturing companies. Measure the area of ​​carbon emissions disclosure using a checklist developed based on the information request sheet provided by the CDP (Carbon Emissions Project). The population and sample in this study are companies listed on the Indonesia stock exchange during the period of 2016, 2017, 2018 using Purposive Sampling. A total of 96 samples were collected over a period of 3 years. The results of this study indicate that Company Size, Enterprise Age, lerveage and Institutional Ownership do not agree with Carbon Emission Disclosures. While profitability have a significant effect on carbon emission disclosure.